1987
DOI: 10.1080/0028825x.1987.10410070
|View full text |Cite
|
Sign up to set email alerts
|

The quantity and nature of the forest floor and topsoil under some indigenous forests and nearby areas converted toPinus radiataplantations in South Island New Zealand

Abstract: In a comparative study, the quantity of accumulated organic matter in, and the nutrient composition of the forest floor and topsoil (0-20 cm) of indigenous (beech or podocarp) forests and nearby Pinus radiata plantations in five widely separated forest sites in the South Island of New Zealand were measured. Total mass of forest floors in native and radiata plantation stands ranged from 25 to 464 and 9 to 79 t/ha, respectively. Native forest stands apparently accumulated larger amounts than nearby radiata pine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…In the top 20 cm of soil, the carbon concentration was higher in the NF and lower in the plantations, suggesting that conversion of native forest and subsequent slashing and burning was accompanied by some carbon loss from the topsoil. Similar results have been reported in a variety of studies [15,16,34,41,42].…”
Section: Detritus Carbon Poolssupporting
confidence: 78%
“…In the top 20 cm of soil, the carbon concentration was higher in the NF and lower in the plantations, suggesting that conversion of native forest and subsequent slashing and burning was accompanied by some carbon loss from the topsoil. Similar results have been reported in a variety of studies [15,16,34,41,42].…”
Section: Detritus Carbon Poolssupporting
confidence: 78%
“…Consideration must be given to the bulk density of the material. No measurements of litter bulk density were made in the present study, but Goh & Heng (1987) reported the average bulk, density of mixed beech litter to be approximately 0.06 g/era 3. Using this value the two methods gave reasonably similar estimates overall for the loss of organic matter during burning.…”
Section: Discussionmentioning
confidence: 80%
“…Weight of the forest floor at three biomass sampling periods (Table 3) shows that results obtained were in the medium range of forest floor weights reported for other West Coast beech forests (Goh & Heng 1987). There were few significant differences in the weights between different treatments.…”
Section: Mass Of the Forest Floormentioning
confidence: 76%
See 2 more Smart Citations